New records of the bats Histiotus montanus and Molossopsneglectus in southeastern Brazil with notes on biology and morphology - Renato Gregorin; Matheus C. S. Mancini; Rafael S. Laurindo; Rodrigo M. Mello; Ligiane M. Moras; Talita G. Almeida; Lilith C. Silva (Caldasia)
Distributional and biological data for some bat species in South America are scarce, mainly in non-phyl-lostomid bats. Herein we provide new records of two rare species of aerial insectivore bats for south-eastern Brazil, Histiotus montanus and Molossops neglectus. In addition, we report facial morphologi-cal variation in color and new records of ectoparasites for H. montanus. For M. neglectus we performed a Principal Component Analysis (PCA) to check for morphometric variation based on forearm and skull dimensions, the southerly distributed specimens showing slightly smaller measurements than the northern ones.